Beyond Words: An Analysis of Illocutionary Acts in Beautiful Boy - Musyari, Revan Anggara (LingPoet: Journal of Linguistics and Literary Research, 2025)
Verbal communication, often considered as a means of conveying information, is actually much more complex and full of meaning. This study aims to classify the types of illocutionary speech acts expressed by the speaker in the movie Beautiful Boy. In this research, a descriptive method with quantitative approach is used. The data were collected using listening and note-taking techniques. Based on the analysis, there are 310 utterances that show illocutionary acts, which are dominated by assertive speech acts with 112 occurrences, followed by other types, namely directive with 98 occurrences, commissive 57 occurrences, expressive 33 occurrences, and declarative 10 occurrences. The tendency of these speech acts is identified to be influenced by the context of the conversation in Beautiful Boy, and not due to the genre of the movie which is drama and biography. The speech acts in this movie describe deep feelings, frustrations, and also hopes that aim to achieve something can have the opposite effect or even the loaded message is not conveyed or in line with the reality faced.